2010
DOI: 10.1016/j.pmrj.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Falling in the Postoperative Lower Limb Amputee While on the Surgical Ward

Abstract: Objective To determine the incidence and risk factors of falling among amputees during the postoperative time on the surgical ward. Design Retrospective cohort. Setting Three tertiary acute care hospitals. Patients Subjects aged 18 years or older undergoing either a primary or revision amputation at the transtibial, knee disarticulation, or transfemoral levels. Subjects were excluded if they underwent bilateral amputations. A total of 466 charts were identified, and 370 subjects were included in the analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 17 publications
(48 reference statements)
5
40
0
Order By: Relevance
“…These individuals must coordinate whole-body movements despite the lack of critical structures, such as the foot, ankle, and more proximal joints. Balance confidence is also decreased in prosthesis users [4,5] and these individuals fall more frequently than age matched controls [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These individuals must coordinate whole-body movements despite the lack of critical structures, such as the foot, ankle, and more proximal joints. Balance confidence is also decreased in prosthesis users [4,5] and these individuals fall more frequently than age matched controls [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half of the lower-limb amputees have experienced a fall at least once within 12 months (Miller et al, 2001). It was also reported that 16.5% of the amputees experienced falls in the hospital and 60.7% of them got injured because of the falls (Yu et al, 2010). One plausible reason explaining the high incidence of falls is that they have poor balance due to the loss of active plantarflexion and dorsiflexion (Hak et al, 2013;Vanicek et al, 2009), which cannot be compensated by prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Although falls are common in individuals with LLAs, it is important to note that the occurrence of falls varies across the care continuum (eg, acute surgical ward after amputation, inpatient rehabilitation, and community living after rehabilitation) . Prospective studies have demonstrated that the percentage of people falling varies from 20.5% in acute hospitals, 35% in inpatient rehabilitation programs, to a high of 42.5% in the first 6 months after discharge from inpatient rehabilitation . Even years after successful completion of inpatient rehabilitation programs, more than half of community‐dwelling adults with an LLA fall at least once a year, with 33% experiencing two or more falls .…”
Section: Introductionmentioning
confidence: 99%
“…Consequences of falls also differ across the phases of care. Falls during inpatient rehabilitation can result in death, injury, a longer length of hospital stay, and greater health care costs . In addition, consequences of falls for community dwellers include limb fracture, fear of falling, lack of prosthesis use, and social withdrawal compared to individuals with LLA who do not fall .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation